Impairment of Intramacrophagic Brucella suis Multiplication by Human Natural Killer Cells through a Contact-Dependent Mechanism - Dornand, Jacques (American Society for Microbiology, 2004)
Brucella spp. are facultative intracellular bacteria that can establish themselves and cause chronic disease in humans and animals. NK cells play a key role in host defense. They are implicated in an early immune response to a variety of pathogens. However, it was shown that they do not control Brucella infection in mice. On the other hand, NK cell activity is impaired in patients with acute brucellosis, and recently it was demonstrated that human NK cells mediate the killing of intramacrophagic Mycobacterium tuberculosis in in vitro infection. Therefore, we have analyzed the behavior of Brucella suis infecting isolated human macrophages in the presence of syngeneic NK cells. We show that (i) NK cells impair the intramacrophagic development of B. suis, a phenomenon enhanced by NK cell activators, such as interleukin-2; (ii) NK cells cultured in the presence of infected macrophages are highly activated and secrete gamma interferon and tumor necrosis factor alpha; (iii) impairment of bacterial multiplication inside infected cells is marginally associated with the cytokines produced during the early phase of macrophage-NK cell cocultures; (iv) direct cell-to-cell contact is required for NK cells to mediate the inhibition of B. suis development; and (v) inhibition of B. suis development results from an induction of NK cell cytotoxicity against infected macrophages. Altogether, these findings show that NK cells could participate early in controlling the intramacrophagic development of B. suis in humans. It seems thus reasonable to hypothesize a role for NK cells in the control of human brucellosis. However, by impairing the activity of these cells in the acute phase of the illness, the pathogen should avoid this control.